3D analysis of applied field effect on trapped magnetic field during pulsed field magnetization of bulk superconductor. Issue 1 (18th April 2014) - Khene, Mohamed Lotfi; Alloui, Lotfi; Mimoune, Souri Mohamed; Bouillault, Frédéric; Feliachi, Mouloud
Abstract : External applied field effect in magnetization process by pulsed field (PFM) method of rectangular bulk superconductor is analysed by solving the A-V magnetic equation coupled to the thermal one in order to show the influence of the amplitude of the external field on the trapped magnetic field of bulk superconductor. A numerical model based on the control volume method (CVM) has been developed, which uses a power-law model with temperature dependency and magnetic field dependence on critical current density. For low cooling temperature T co  = 20 K, a good distribution of the trapped magnetic field of the bulk superconductor is obtained when we applied high external field.